Optimal investments in Africa's road network - Sebastian Krantz (Kiel Institute for the World Economy (IfW Kiel), 2024)
This paper characterizes economically optimal investments into Africa's road network in partial and general equilibrium - based on a detailed topography of the network, road construction costs, frictions in cross-border trading, and economic geography. Drawing from data on 144 million trans-continental routes, it first assesses local and global network efficiency and market access. It then derives a large network connecting 447 cities and 52 ports along the fastest routes, devises an algorithm to propose new links, analyzes the quality of existing links, and estimates link-level construction/upgrading costs. Subsequently, it computes market-access-maximizing investments in partial equilibrium and conducts cost-benefit analysis for individual links and several investment packages. Using a spatial economic model and global optimization over the space of networks, it finally elicits welfare-maximizing investments in spatial equilibrium. Findings imply that cross-border frictions and trade elasticities significantly shape optimal road investments. Reducing frictions yields the greatest benefits, followed by road upgrades and new construction. Sequencing matters, as reduced frictions generally increase investment returns. Returns to upgrading key links are large, even under frictions.
Keywords: O18; R42; R10; O10; 330; African roads; spatially optimal investments; big data; PE and GE analysis